Evaluasi Pembinaan Prestasi Pada Cabang Olahraga Paralayang Di Jawa Tengah Tahun 2024 - Adityatama, Muhammad Nurul Akbar; Binathara, Muhammad Bagus (STAMINA, 2024)
The main objective of this research is to evaluate the context, input, management, and outcomes in the development of paragliding performance in Central Java in 2024. The evaluation instrument used is the CIPP model. The subjects of this study include managers, instructors, athletes, and the parents of paragliding athletes in Central Java. Data collection methods include observation, interviews, questionnaires, and documentation. Data analysis was carried out using both quantitative and qualitative descriptive approaches. The findings indicate that overall, the evaluation of the paragliding development program in Central Java falls into the good category. This includes: (1) The context component, which was rated very good; (2) The evaluation of the input component; (3) The evaluation of the process component; and (4) The product component, which was also rated very good. The product evaluation shows that the performance results of Central Java's paragliding athletes are satisfactory, as demonstrated by various achievements that have been obtained.